Uncommon Presentation of Perianal Condyloma Acuminata in a Young Male: A Case Report - Christina, Natalia Maria; Prasetyo, Patricia Diana; Cendikiawan, Albert; Wijaya, Jeremiah Hilkiah (Medicinus, 2024)
Background: Perianal warts, also known as anogenital warts or condyloma acuminata, represent a significant health concern in the young male population. Here, we present a unique case of a large perianal wart in a 26-year-old male patient.Case Description: The patient came to the surgical clinic with complaints of an anal lump for 7 months ago. The lump first appeared in February 2019 as big as a green bean, it increased in size, bled easily and painful to be touched. The patient had a history of anal intercourse 1 month before the lump appeared. The lump size was about 8 x 5 cm and resembled “cauliflower”. Diagnosis of suspected anal papilloma was made.  In July 2019, an incisional biopsy was performed, and the result showed papilloma squamosa with condyloma acuminata as a differential diagnosis. In September 2019, perianal soft tissue tumor excision with advancement flap was performed and the result showed condyloma acuminata. Discussions: The case highlights the importance of careful evaluation and diagnosis in such clinical scenarios, as the initial diagnosis of anal papilloma was later refined to condyloma acuminata based on the biopsy and surgical findings. Early detection and appropriate management are crucial in cases like this to ensure the best possible patient outcomes.